Evaluation of the Problems Encountered by Families with Children with Autism After Compulsory Education from the Perspective of Social Work and Suggestions for Solutions - Alp Koçer; Fatih Kucur (Sosyal Siyaset Konferansları Dergisi)
The increasing number of children with autism increases the need for services for individuals who are adults with autism. In Turkey, services in the field of education for people with autism are limited to public school programs. As a result, the goal of the study is to assess the challenges faced by families with children with autism during the post-secondary education process from the perspective of social work and to propose solutions based on social work principles. The phenomenological research design, which is one of the qualitative research designs, was used in the research. The study group of the research consists of families whose children with autism are over the age of 18 and have completed compulsory education. By these criteria, interviews were conducted with a total of 16 families, 15 in Istanbul and 1 in Izmir. The findings of the interviews were collected with a semi-structured interview form and interpreted with descriptive analysis. This study revealed that families with autistic children face many different problems during the post-compulsory education process such as staying at home, problems in finding and applying to institutions, the inadequacy of education, educators, and course hours in institutions and families are left alone, and they need various services and practices to solve these problems.